Once-weekly prophylactic treatment vs. on-demand treatment with nonacog alfa in patients with moderately severe to severe haemophilia B - Kavakli, K.; Smith, L.; Kuliczkowski, K.; Korth-Bradley, J.; You, C. W.; Fuiman, J.; Zupančić-Šalek, S.; Abdul Karim, F.; Rendo, P. (Haemophilia : the official journal of the World Federation of Hemophilia, 2016)
Introduction Limited data are available on optimal prophylaxis regimens of factor IX (FIX) replacements for patients with haemophilia B. Aim This multicentre, open‐label study evaluated the efficacy and safety of once‐weekly prophylaxis with nonacog alfa compared with on‐demand treatment in adolescent and adult patients. Methods Males aged 12–65 years with moderately severe to severe haemophilia B (FIX:C ≤ 2%) were eligible for enrolment. Patients received on‐demand treatment for 26 weeks, followed by once‐weekly prophylaxis of 100 IU kg−1 for 52 weeks. The primary efficacy end point was the annualized bleeding rate (ABR). Secondary end points included response to on‐demand treatment, the number of infusions used to treat bleeding events, and the incidence of less‐than‐expected therapeutic effect (LETE). FIX:C was measured on day 1 and at weeks 26 and 78. Results Mean (±SD) ABR was lower during prophylaxis vs. on‐demand treatment [3.6 (±4.6) vs. 32.9 (±17.4) events, respectively; P < 0.0001]. The majority (88.4%) of bleeding events had excellent or good responses upon the first infusion; 82.1% of events responded to the first infusion. No incident of LETE occurred. No thrombotic events or FIX inhibitors were reported. Eight of 17 FIX:C approximately 1 week after dosing were >2 IU dL−1 (min–max of 2.13–10.39 IU dL−1). Conclusions Once‐weekly prophylaxis of 100 IU kg−1 was associated with lower ABR compared with on‐demand treatment in adolescents and adults with moderately severe to severe haemophilia B. Once‐weekly prophylaxis was well tolerated, with a similar safety profile as that reported during the on‐demand treatment period. Residual FIX:C may be supportive of effectiveness.